2017
DOI: 10.1038/s41598-017-06354-1
|View full text |Cite
|
Sign up to set email alerts
|

The interfacial pH of acidic degradable polymeric biomaterials and its effects on osteoblast behavior

Abstract: A weak alkaline environment is established to facilitate the growth of osteoblasts. Unfortunately, this is inconsistent with the application of biodegradable polymer in bone regeneration, as the degradation products are usually acidic. In this study, the variation of the interfacial pH of poly (D, L-lactide) and piperazine-based polyurethane ureas (P-PUUs), as the representations of acidic degradable materials, and the behavior of osteoblasts on these substrates with tunable interfacial pH were investigated in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
35
0
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 41 publications
(36 citation statements)
references
References 45 publications
0
35
0
1
Order By: Relevance
“…Additionally, pins obtained from decellularized human or bovine cortical bone have been described [19]. However, the application of these resorbable pins has been associated with different issues, such as a low biocompatibility (e.g., due to the degradation products) or a lack of mechanical functionality for maintaining a secure fixation [26][27][28].…”
Section: Introductionmentioning
confidence: 99%
“…Additionally, pins obtained from decellularized human or bovine cortical bone have been described [19]. However, the application of these resorbable pins has been associated with different issues, such as a low biocompatibility (e.g., due to the degradation products) or a lack of mechanical functionality for maintaining a secure fixation [26][27][28].…”
Section: Introductionmentioning
confidence: 99%
“…The use of cross-linking agents with different functionality mixed with polyols that are the primary raw materials of the aqueous phase leads to the preparation of PU materials with hydrophilic surfaces that can enhance the osteogenic differentiation [ 20 ]. This modification of the hydrophilic character improves the aqueous solubilization of PU drug carriers and leads to a more intense therapeutic effect of active substances with low water solubility.…”
Section: Discussionmentioning
confidence: 99%
“…8 . These higher properties were explained by a stable neutral pH over time via PDLLA acidic degradation products neutralization by piperazine [ 240 , 241 ]. They also demonstrated that cell behavior regulation can potentially be achieved by SMP stretching-induced nanostructure [ 242 ].…”
Section: Biobased Pu For Biomedical Applicationsmentioning
confidence: 99%